REPRESENTASI FEMINISME DALAM IKLAN KECAP ABC “SUAMI SEJATI MAU MASAK” - Rozi, Ferdial Fahrul; Rasyid, Abdul (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The kecap ABC advertisement for the suami Sejati Mau Masak edition is a series in the gender equality campaign created by Heinz ABC Indonesia. Through this series of advertisements, it is made as a form of appreciation to women who have done domestic work, especially cooking. In this ad, many messages of feminism are shown visually in every scene. The purpose of this research is to analyze how the message of feminism is contained in the Ketchup ABC advertisement of “suami sejati mau masak” using Rolnad Barthes's semiotic theory approach. In this study, it was carried out using descriptive qualitative research methods by collecting data, conducting analysis, making discussions and conclusions. The results of this study are an analysis of various scenes from the ABC soy sauce of Suami Sejati Mau Masak which is considered to have a feminist message using Roland Barthes's theoretical approach discussing denotative, connotative and myth development.